Studi Empiris Hubungan Kesadaran Konsumen, Sikap Konsumen Dan Kepuasan Konsumen terhadap Intensitas Pembelian Produk Handicraft Daur Ulang - Yayuk Sriayudha; Suswita Roza; Sylvia Kartika Wulan Bhayangkari; Ade Octavia (Universitas Batanghari, 2022)
Recycled products are sustainable products designed to minimize environmental impact throughout their life cycle. The purpose of product development through the manufacture of recycled handicrafts is to reduce the effect of pollution, reduce plastic waste and maximize resource efficiency. The increased purchasing intensity of recycled handicraft products is inseparable from the basic theory that explains the relationship between consumer attitudes and purchase intention. This study aims to (1) analyze and explain the effect of environmental awareness and consumer attitudes on the intensity of purchasing recycled handicraft products, (2) analyze and explain the influence of environmental awareness and consumer satisfaction and the intensity of purchasing recycled handicraft products and (3) analyze and explain the effect of consumer awareness on the intensity of purchasing recycled handicraft products. The study used a quantitative research design. The population in this study are consumers of recycled handicraft products in Jambi Province. The questionnaire prefers as a research instrument for 200 samples. The statistical model used is the Structural Equation Model (SEM) of Variance with the SmartPLS analysis tool. The study showed that consumer awareness significantly influences attitudes and satisfaction with recycled handicraft products. A significant influence is also seen in consumer satisfaction and purchase intensity. But on the other hand, the study results showed no significant effect between consumer awareness and satisfaction on the intensity of purchasing recycled handicraft products. It is hoped that the research results can be a reference for consumers, the wider community, MSME actors, academics who conduct similar research, and the government as strategic policymakers.